Predicting complications and morbidities in PAD patients through lower extremity compositions with dual-energy CT and material decomposition: a 2-year follow-up observational study - Lin, Dao-Chen; Tsai, Pei-Shan; Lin, Tzu-Lin; Huang, Wen-Hui; Liu, Yu-Peng; Wu, Tung-Hsin; Shih, Cheng‑Ting (BMC cardiovascular disorders, 2025)
Peripheral artery disease (PAD) is associated with various morbidities. This study aims to investigate the correlation between different lower extremity compositions and development of morbidities in PAD patients. Between January 2018 and December 2020, 108 subjects diagnosed of PAD were enrolled (mean age of 64.1 ± 13.5 years) and utilized dual-energy computed tomography (DECT) with material decomposition to measure the vessel volume, muscle volume, fat volume, and cortical-bone volume in lower extremity respectively. The association between each leg composition and developing complications or morbidities in PAD patients was analyzed over a two-year follow-up. Fontaine stage 3 and 4 had lower muscle mass compared to stages 1 and 2. More severe vascular stenosis was associated with lower muscle, fat, and cortical-bone volume. Patients with severe Fontaine stages (3 and 4) and lower-leg vascular stenosis had a higher risk of developing infection or inflammation (OR 45.5, 95% CI: 13.5-166.7, and OR 11.7, 95% CI: 2.8-50, P < 0.05) and amputation (OR 18.2, 95% CI: 2.2-142.8, and OR 10.7, 95% CI: 1.11-100, P < 0.05). Lower thigh cortical-bone volume was associated with an increased risk of falls resulting in fractures (OR: 1.39, 95% CI: 1.13-2.19, P < 0.01). Thigh cortical-bone volume below 64.5 cm was identified as the cut-off value to predict fall-related fractures, with a sensitivity of 100% and specificity of 92%. This study demonstrates the potential of DECT with material decomposition to assess lower extremity composition and its relevance in predicting complications and morbidities in PAD patients. Severe vascular stenosis may contribute to muscle wasting and subsequent complications, while lower thigh cortical-bone mass may serve as a predictor of fall-related fractures.